Non-Functional Properties in Service Oriented Architecture – A Consumer’s Perspective - Becha, Hanane; Amyot, Daniel (Université d'Ottawa | University of Ottawa, 2012)
Information about non-functional properties (NFPs) is rarely explicitly described in Service Oriented Architecture (SOA) services. In particular, there is still no standardized solution addressing what service providers should expose or advertise as NFPs in service descriptions to empower service consumers to decide whether a given service suits best their needs or not. Our goal is to define a catalogue of generic (i.e., domain independent) non-functional properties to be considered when service descriptions are developed. This catalogue should be used to better characterize services and enable consumers to perform advanced applications such as NFP-aware service selection. We have identified an initial catalogue of SOA-related NFPs that are relevant from the perspective of consumers (as opposed to providers). Then, we have designed an online survey and invited international SOA experts in many application areas to criticize the relevance and definitions of the proposed NFPs and to enhance this catalogue. After analyzing the survey results to synthesize an improved catalogue, we have validated the new definitions a second time with a subset of the initial participants. We obtained a validated list of 17 NFP definitions for atomic SOA service descriptions relevant from a service consumer's perspective.
Keywords: Service Oriented Architecture (SOA); Service Description; Non-Functional Properties (NFPs); Consumer’s Perspective